2018
DOI: 10.1002/ejhf.1339
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction and cellular repair in heart failure with preserved ejection fraction: response to a single maximal exercise bout

Abstract: Aims -Endothelial dysfunction contributes to exercise intolerance in heart failure with preserved ejection fraction (HFpEF). Endothelial progenitor cells (EPC) and angiogenic T lymphocytes (TA) participate in endothelial repair. Recruitment of EPC or TA with exercise might explain the vascular benefits of exercise training. We studied baseline endothelial function, EPC and TA numbers in HFpEF patients and the effects of a single exercise bout.Methods and Results -HFpEF patients (n=26) and age-and sex-matched h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 39 publications
2
23
0
2
Order By: Relevance
“…TAs secrete high amounts of pro-angiogenic factors (vascular endothelial growth factor, IL-8) and are thought to participate in endothelial repair through paracrine control of EPCs via CD184 (Walter et al., 2005). We have recently shown that numbers of circulating EPCs and TAs are reduced in HFpEF patients, indicating a deficient endothelial repair (Gevaert et al., 2019). Restoring endothelial regenerative capacity could be a future target in HFpEF research.…”
Section: Cellular Alterations Underlying Structural and Functional Chmentioning
confidence: 99%
See 1 more Smart Citation
“…TAs secrete high amounts of pro-angiogenic factors (vascular endothelial growth factor, IL-8) and are thought to participate in endothelial repair through paracrine control of EPCs via CD184 (Walter et al., 2005). We have recently shown that numbers of circulating EPCs and TAs are reduced in HFpEF patients, indicating a deficient endothelial repair (Gevaert et al., 2019). Restoring endothelial regenerative capacity could be a future target in HFpEF research.…”
Section: Cellular Alterations Underlying Structural and Functional Chmentioning
confidence: 99%
“…In short, vascular function in large and medium-size vessels seems relatively preserved in HFpEF patients. However, almost all studies comparing microvascular endothelial function between HFpEF patients and matched healthy volunteers show a microvascular endothelial dysfunction in HFpEF (Borlaug et al., 2010; Akiyama et al., 2012; Lee et al., 2016; Gevaert et al., 2019).…”
Section: Cellular Alterations Underlying Structural and Functional Chmentioning
confidence: 99%
“…Fifteen clinical trials examined the acute effects to exercise (Adams et al 2004 ; Shaffer et al 2006 ; Van Craenenbroeck et al 2009 ; Van Craenenbroeck et al 2010a ; Sandri et al 2011 ; Van Craenenbroeck et al 2011 ; Rummens et al 2012 ; Scalone et al 2013 ; Kazmierski et al 2015 ; Rocha et al 2015 ; West et al 2015 ; Lutz et al 2016 ; Waclawovsky et al 2016 ; Gevaert et al 2019 ; Kourek et al 2020b ) (Table 1 ). Thirteen trials included independent groups before and after (Adams et al 2004 ; Shaffer et al 2006 ; Van Craenenbroeck et al 2009 ; Van Craenenbroeck et al 2010a ; Van Craenenbroeck et al 2011 ; Rummens et al 2012 ; Scalone et al 2013 ; Kazmierski et al 2015 ; Rocha et al 2015 ; West et al 2015 ; Lutz et al 2016 ; Gevaert et al 2019 ; Kourek et al 2020b ), one was a single arm trial (Sandri et al 2011 ) and another one a randomised cross over trial (Waclawovsky et al 2016 ). Across the 15 included trials (649 participants), 13 reported percentages of male and female distribution (Van Craenenbroeck et al 2009 ; Van Craenenbroeck et al 2010a ; Sandri et al 2011 ; Van Craenenbroeck et al 2011 ; Rummens et al 2012 ; Scalone et al 2013 ; Kazmierski et al 2015 ; Rocha et al 2015 ; West et al 2015 ; Lutz et al 2016 ; Waclawovsky et al 2016 ; Gevaert et al 2019 ; Kourek et al 2020b ).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, as a secondary outcome four trials measured the number and/ or function of cultured myeloid angiogenic cells (MACs) defined as double positive for acetylated Low-Density Lipoprotein labelled with 1,1′-dioctadecyl-3,3,3′,3′-tetramethylindocarbocyanine perchlorate and lectin (Di-acLDL + / lectin + cells) (Adams et al 2004;. Ten out of the 15 trials (Table 2) predominantly included two blood collection time points for circulating EPCs with the post-exercise time point varying between immediately post-exercise and 24 h post-exercise (Shaffer et al 2006;Van Craenenbroeck et al 2009;Van Craenenbroeck et al 2010a;Rummens et al 2012;Scalone et al 2013;Rocha et al 2015;Lutz et al 2016;Waclawovsky et al 2016;Gevaert et al 2019;Kourek et al 2020b). The most common time point adopted in the majority of trials was 10 min post-exercise.…”
Section: Acute Clinical Trial Characteristics and Intervention Detailsmentioning
confidence: 99%
“…The endothelium is a self-renew system; however, disruption of the injury and repair balance of endothelium will lead to the pathophysiology of vascular diseases. The endothelial injury can be repaired by endothelial cell proliferation, the differentiation of endothelial progenitor cells (EPCs) to endothelial cells, and other mechanisms [66,67]. There is a study in 1997 showing for the first time that human peripheral blood-derived EPC is one kind of stem cells which plays important role in endothelial repair and angiogenesis [68].…”
Section: The Beneficial Effects Of Exercise On Endothelial Progenitor Cellsmentioning
confidence: 99%